Pengembangan Media Kartu Kamal dalam Penguasaan Kosakata Bahasa Arab - M. Syamsul Ma'arif (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2019)
Vocabulary is one element of language that must be mastered by learners in mastering a particular language including Arabic. Learning Arabic vocabulary requires its own strategies so that the learning will not be boring, one of them is a card games. This study aims to develop Arabic vocabulary learning media in the form of cards named